Coaching and mentoring for academic development - Guccione, Kay; Hutchinson, Steve (Surviving and thriving in academia., 2021)
Learning through dialogue brings a powerful opportunity to navigate professional demands and meet the challenges of a turbulent world. Written for all who mentor or coach in universities, this book addresses a critical question: how can mentoring and coaching be an effective and accessible way to support researcher and academic development?